Using partner notification to address curable sexually transmitted infections in a high HIV prevalence context: a qualitative study about partner notification in Botswana - Adriane Wynn; Corrina Moucheraud; Neo Moshashane; Ogechukwu Agatha Offorjebe; Doreen Ramogola-Masire; Jeffrey D. Klausner; Chelsea Morroni (BMC, 2019)
Abstract Background Partner notification is an essential component of sexually transmitted infection (STI) management. The process involves identifying exposed sex partner(s), notifying these partner(s) about their exposure to a curable STI, and offering counselling and treatment for the STI as a part of syndromic management or after results from an STI test. When implemented effectively, partner notification services can prevent the index patient from being reinfected with a curable STI from an untreated partner, reduce the community burden of curable STIs, and prevent adverse health outcomes in both the index patient and his or her sex partner(s). However, partner notification and treatment rates are often low. This study seeks to explore experiences and preferences related to partner notification and treatment for curable STIs among pregnant women receiving care in an antenatal clinic with integrated HIV and curable STI testing. Results are intended to inform efforts to improve partner notification and treatment rates in Southern Africa. Methods We conducted qualitative interviews among women diagnosed with Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and/or Trichomonas vaginalis (TV) infection while seeking antenatal care in Gaborone, Botswana. Semi-structured interviews were used to obtain women's knowledge about STIs and their experiences and preferences regarding partner notification. Results Fifteen women agreed to participate in the study. The majority of women had never heard of CT, NG, or TV infections prior to testing. Thirteen out of 15 participants had notified partners about the STI diagnosis. The majority of notified partners received some treatment; however, partner treatment was often delayed. Most women expressed a preference for accompanying partners to the clinic for treatment. Experiences and preferences did not differ by HIV infection status. Conclusions The integration of STI, HIV, and antenatal care services may have contributed to most women's willingness to notify partners. However, logistical barriers to partner treatment remained. More research is needed to identify effective and appropriate strategies for scaling-up partner notification services in order to improve rates of partners successfully contacted and treated, reduce rates of STI reinfection during pregnancy, and ultimately reduce adverse maternal and infant outcomes attributable to antenatal STIs.